KECENDERUNGAN PERILAKU MEROKOK PADA SISWA DITINJAU DARI CARA MENDIDIK OTORITER DAN PENGARUH NEGATIF TEMAN SEBAYA - Mahardika, Gustin Ratu; Mudjijanti, Fransisca (Educatio Vitae, 2015)
Family is the most influential factor in the development of children and adolescents. The family has an important role in the formation of personality. The period of adolescence is a period of transition from childhood to adulthood. Changes that occur, often bring a certain impact on an adolescent self. This study aimed to determine the effect of smoking on student behavior tendencies in terms of how to educate the authoritarian and the negative influence of peers. The population in this study were students of class X SMK Yosonegoro Magetan academic year 2013/2014 the number of 16 classes and sampling as much as 5 classes. The sampling technique used is cluster sampling. Data were collected using a questionnaire form scale. Questionnaire form of scale that smoking behavior scale, scale and scale to educate authoritarian negative influence of peers. In this study, the authors propose three hypotheses, namely: 1) there is a significant effect on the tendency to educate authoritarian smoking behavior in students. 2) There is a significant effect of the negative influence of peers on the trend of smoking behavior in students. 3) There is a significant effect of educating authoritarian manner and the negative influence of peers on the trend of smoking behavior in students. Data were analyzed using multiple linear regression techniques. Based on the results of data processing can be summarized as follows: 1) model regression equation Y = 13 654 + 0429 (X1) + 0.291 (X2). 2) Correlation analysis showed R of 0840 means to educate the authoritarian and the negative influence of peers has a very strong closeness to the tendency of smoking behavior. 3) The coefficient of determination for 0706, it is meant to educate the authoritarian and the negative influence of peers has the effect of 70.6% by the trend of smoking behavior. 4) Hypothesis "There is a significant effect on the tendency to educate authoritarian smoking behavior in students' accepted. 5) Hypothesis "There is a significant negative influence of peers on the trend of smoking behavior in students' accepted. 6) Hypothesis "There is a significant effect of educating authoritarian manner and the negative influence of peers on the trend of smoking behavior.Keywords: smoking behavior, how to educate authoritarian, and the negative influence of peers